Wound Healing and Acute Dermal Toxicity Studies of Ludwigia octovalvis (Jacq.) P. H. Raven (Onagraceae) in Sprague–Dawley Rats - Martin Boadi; Stephen Yao Gbedema; Yaw Duah Boakye; Marcel Tunkumgnen Bayor; Eugene Agyei Aboagye (Journal of Tropical Medicine)
Introduction. The aerial part of Ludwigia octovalvis has been used traditionally in some parts of Asia for the management of wounds owing to the presence of phytochemicals such as tannins, flavonoids, and triterpenoids among others. The incidence of wounds, their associated complications, and the cost of wound care are on the increase globally, therefore, the need to develop alternative wound care agents. The aim of this study was to scientifically investigate the wound healing potential of the ethanolic extract of L. octovalvis using the excision wound healing model in rats and also carry out an acute dermal toxicity investigation of the plant extract. Method. A 70% ethanol extract of L. octovalvis was prepared for the wound healing activity using the excision wound healing model in Sprague–Dawley rats. Aqueous creams (1, 3, and 10%) were prepared and topically applied to the wounds once daily according to the groups of animals. The wounds were assessed for rates of wound closure on days 3, 5, 7, 9, and 11. Re-epithelialization periods were also determined. Sections of wound tissues obtained on day 13 were subjected to histological investigations. An acute dermal toxicity of the plant extract was investigated. Results. L. octovalvis treatment (1, 3, and 10%) exhibited a mean percentage wound contraction range of 85.36 ± 7.22–94.14 ± 2.23 on day 11. The extract exhibited re-epithelialization periods of 17.3 ± 1.2, 19.8 ± 2.6, and 16.0 ± 1.7 days for the 1, 3, and 10% extract creams, respectively, whereas the cream-only and 1% silver sulfadiazine treatments resulted in a re-epithelialization period of greater than 28 days. Histopathological investigation revealed enhanced fibroblast infiltration and collagen deposition in the treatment groups. No adverse reaction was observed in the acute dermal toxicity study. Conclusions. Extract of L. octovalvis exhibited wound healing by enhancing wound contraction, re-epithelialization, fibroblast infiltration, and collagen deposition at the wound site. The extract did not exhibit any toxic reaction in the acute dermal toxicity study.